The Effect of E-Filing, Tax Socialization and Understanding of Tax Regulations on People's Trust Which Impacts on Individual Taxpayer Compliance Using SEM-PLS - Monica Pongsibidang; Erni Susanty; Jerry Heikal (CV. Green Publisher Indonesia, 2025)
This research aims to determine whether the application of the e-filing system, tax socialization, and understanding of tax regulations affect the level of public trust, which in turn impacts individual taxpayer compliance. The analysis method used is multiple linear regression analysis with the SEM-PLS program on SmartPLS 4.0 software. Based on the processing results, a significant P value and original value were found between variable X and variable Y1, namely the understanding of tax regulations, which has a significant effect on people's trust. Additionally, variable X and variable Y2, the application of the e-filing system, significantly affect taxpayer compliance. It can be concluded that the most influential factor in this study is increasing public understanding of tax regulations; as taxpayer trust in the government rises, implementing the e-filing system also enhances taxpayer compliance. This study proves that with a general understanding of tax regulations, taxpayer trust in the government increases, leading to higher taxpayer compliance. The relationship between the level of trust in the government and taxpayer compliance has a positive and proportional effect; conversely, if taxpayer trust decreases, taxpayer compliance will negatively be affected. The results also show that the application of the e-filing system positively influences tax compliance. It can be concluded that taxpayers who are aware of the e-filing system and can access the tax system anytime and anywhere find it easier to report their taxes, thereby encouraging greater adherence to their tax obligations.